Relationship between parental involvement and children’s positive mental character during early years: the moderating role of parent-teacher relationship and teacher-parent relationship - Cai, Liman; Huang, Peishan; Guo, Yuanfang (Frontiers in Psychology, 2024)
Introduction To explore the association between parental involvement and children’s positive mental character, and examine the moderating effect of the relationship between teachers and parents. Methods The present study conducted latent moderated structural equation model among 167 Chinese preschool teachers and 1019 preschool children and their parents. Parents reported children’s positive mental character and perceived relationships with their children’s teachers while teachers reported their perceived relationships with each child’s parents. Results The results indicated that (1) three dimensions of parental involvement (home-based involvement, school-based involvement and home-school conferencing) were positively related to children’s positive mental character; (2) teacher-perceived teacher-parent relationship moderated the association between home-based involvement and children’s positive mental character; (3) the effects of school-based involvement * parent-teacher relationship and home-school conferencing * parent-teacher relationship on children’s positive mental character were significant. Discussion This study provided the implications for promoting the development of positive mental character among Chinese preschool children.